2003
DOI: 10.1177/1523422303005002006
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Culture of Learning in a Changing Industrial Climate: An Australian Case Study

Abstract: The problem and the solution. An organization that does not have a history of being a learning organization but has experienced generally confrontational industrial relations began to change its learning culture. This study suggests that even without a systematic approach, some of the features of a learning organization can develop through efforts at the individual and the systemic levels but that the issue of power relationships in the organization is highly significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
4
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 5 publications
5
16
4
7
Order By: Relevance
“…Dymock, 2003;Watkins and Marsick, 2003). Taken together, the consistency with previous research attests to the validity of the proposed definitions and empirical indicators of what constitutes an enabling and a constraining learning environment.…”
Section: Discussionsupporting
confidence: 74%
“…Dymock, 2003;Watkins and Marsick, 2003). Taken together, the consistency with previous research attests to the validity of the proposed definitions and empirical indicators of what constitutes an enabling and a constraining learning environment.…”
Section: Discussionsupporting
confidence: 74%
“…This suggests that for the most part, the officers had a neutral perception of their organization as one that promotes learning practices, a learning culture, and continuous learning with a mean at an individual level of 3.26, at the team level 3.10, and at the organizational level 3.40. Conversely, other studies conducted using the DLOQ-A in the international arena indicated that employees perceived their organization as one that promotes learning (Dymock, 2003;Hernandez, 2003;Weldy & Gillis, 2010). However, in this study, the officers did not perceive their organization as one that did or did not promote learning.…”
Section: Research Questioncontrasting
confidence: 52%
“…Dotychczas kwestionariusz został przetłumaczony na 14 języków, a na podstawie badań przeprowadzonych przy jego użyciu powstało ponad 70 artykułów naukowych (Watkins i O'Neil, 2013, s. 139). Ze względu na liczne zastosowanie w stosunku do pojedynczych firm (Dymock, 2003;Hasson, Tafvelin i von Thiele Schwarz, 2013;Song, Joo i Chermack, 2009), małych i średnich przedsiębiorstw (Kim i Marsick, 2013), przedsiębiorstw państwowych (Sharifirad, 2011;Zhang, Zhang i Yang, 2004), instytucji sek-Źródło: opracowanie własne.…”
Section: Przekrojowe Problemy I Perspektywy Nauk O Zarządzaniuunclassified